The International Judicial Cooperation in Criminal Matters and Its Role in Creating of the European Space of Freedom, Security and Safety (Kriminalističke teme, 2017)
Reason for writing and research problem(s): Nowadays, crimes are one of the greatest threats to the people’s freedom and security. It has become a phenomenon that often exceeds the boundaries of a single state, achieving a cross-border character and giving rise to real organized crime networks. Faced with this challenge, the ac- tions of one state are often not enough to efficiently fight against organised crime, and it needs an international cooperation between states. This international cooperation often takes the form of bilateral or multilateral agreements in which two main areas can be identified on which it is developing. Firstly it focuses on a joint action to criminalize grave acts and establish criminal penalties. We are talking here about serious crimes which affect a lot of people from different states like: drug trafficking, money laundering, criminal offences affecting the states financial interests, environmental crime, etc. Secondly a specialized institutions is necessary to be set up to fight against these kind of crimes and to develop clear rules to better help the coo- peration between states’ judicial institutions. All this cooperation must be based on a mutual trust between states, which is a fundamental principle in the matter. Even though Romania is part of a lot of conventions, the most important thing is that it is a member state of The European Union which pays a special attention to the cooperation in criminal matters.Aims of the paper (scientific and/or social): The aim of this article is to highlight the main mechanisms through which the international cooperation in criminal matters works and indicate future directions to be followed, because a safe space without a close cooperation between states can not really be created.Methodology/ Design: In order to obtain the aims of the paper we will use the analytical method. We will present and analyse the most important institutions and mechanisms implied in international cooperation, and after that, based on those facts, we will try to find new solutions to improve this area.Research/ Paper limitation: The research will focus on the most important institutions as well as on the most important case-law at the European level.Results/ General Conclusion: The international cooperation in criminal matters must be based on the principle of mutual trust.Research/Paper Validity: The reason for writing this article lays in the need to improve the functioning of the international cooperation in criminal matters in order for the criminal phenomenon at the European level to be stopped. That is why, the following paper shall investigate the most important institutions within the international judicial cooperation mechanism framework and highlight the aspects that make the procedures difficult in practice. By finding and highlighting the problems, as well as by a correct understanding of the principles that govern this field, we will, in the end be able to suggest improvement solutions of the international cooperation in criminal matters.